THE CONCEPT OF E-NOTARY IN THE LEGAL SYSTEM OF UKRAINE: PROSPECTS AND RISKS - VDOVICHENA, LYDIA; LUKIIAN, DANA (Ehrlich’s Journal, 2024)
The article examines the concept of “E-notary” from two sides: the positive side and the side of risks of its application. It is established that the introduction of electronic notary combines traditional notarial functions with modern technologies. As a result, the introduction of digital technologies into the notarial system of the State has a two-pronged aspect: the authorities of a notary and the technologies of notarial activity. Traditionally, the law defines a “notary” as a person authorised by the state to execute notarial activities. At the same time, today’s practice shows that, for example, electronic digital signatures and electronic information exchange systems are quite common means of demonstrating the use of digital technologies in notaries, and thus forming elements of the e-notary concept. The authors determine that Ukrainian legislation establishes the basis for the use of digital technologies in notarial activities with the purpose of improving the efficiency, accessibility and security of notarial acts. The main purpose of such a legal approach to E-notary is to use modern electronic means and digital tools to simplify and automate processes related to notarial activities. The main advantages of the E-Notary concept include the ability to minimise both time resources and financial costs, both at the individual and public-institutional levels – the economic context of digitalisation is quite clear from the perspective of both public institutions and the consumer of public services – providing and receiving quality services at minimal cost. The concept of “E-notary” implies that a person carrying out activities in the field of electronic notary has specialised skills in the field of law and computer technology. It also provides for the adaptation of the use of electronic services by notaries in cyberspace or online in the performance of their duties and powers. In order to improve the competence of notaries in the field of information technology, it is necessary to have an appropriate regulation-standard that will be agree at the appropriate governmental level. The authors substantiate that the introduction of the E-notary concept is not only a general need for people entering into relations connected with the performance of notarial acts, but also the protection of notaries and strengthening the defence and security of the State. Therefore, the risks of implementing the E-notary system should also be taken into account, in particular: the existence of information threats, both internal and external (e.g. cyberattacks, unauthorised entry); lack of awareness of consumers of notarial services in this area, which is why the validity of an act performed in the E-notary system is often questioned; the possibility of disclosure of confidential data obtained as a result of notarial activities. The concept of “E-Notary” is not just about digitising the notary’s duties, it is about adding value to electronic notarial documents.